BACTERIA CARRIED BY ANTS IN HEALTH-RELATED ENVIRONMENTS - Couto, Meg Caroline do; Xavier, Raiane Teixeira; Ferro Hein, Milene Moreno; Favero Lisboa, Helen Cristina [UNESP] (Univ Vale Paraiba-univap, 2021)
The presence of ants in health environments can pose risks to humans, considering they can act as a vehicle for the dissemination of several potentially pathogenic microorganisms. In this context, the study aimed to isolate and identify microorganisms carried by ants present in health-related environments. It is an exploratory research, of applied nature, using a quantitative approach. Ants were collected in the ward of an Emergency Care Unit and a long-term care institution for the elderly located in a municipality in the southern region of Mato Grosso. The specimens were attracted with baits (guava, honey and sugar) placed in sterile Petri dishes and kept in the place for a period of 3 hours. The captured ants were placed in liquid culture medium for the preculture of microorganisms. Subsequently, an aliquot of the culture was cultivated on blood agar and Mueller Hinton agar in order to obtain pure culture and they were then evaluated for morphotintorial classification (Gram). The colonies of Gram-positive cocci were subjected to tests for the differentiation between Staphylococcus and Streptococcus and the Gram-negative bacilli were evaluated for carbohydrate fermentation. Fourteen bacterial strains were isolated: 7% Streptococcus pneumoniae, 43% Coagulase-negative Staphylococcus, and 50% Gram-negative bacilli (21.5% fermenters and 28.5% non-fermenters). The results obtained show the vectorial action of ants in the transport of bacteria, many of which are pathogenic, suggesting that such insects may represent a potential health risk.
Keywords: Ants; Bacteria; Health